2022
DOI: 10.1002/advs.202105809
|View full text |Cite
|
Sign up to set email alerts
|

Acoustofluidic Stimulation of Functional Immune Cells in a Microreactor

Abstract: The cytotoxic response of natural killer (NK) cells in a microreactor to surface acoustic waves (SAWs) is investigated, where the SAWs produce an acoustic streaming flow. The Rayleigh-type SAWs form by an interdigital transducer propagated along the surface of a piezoelectric substrate in order to allow the dynamic stimulation of functional immune cells in a noncontact and rotor-free manner. The developed acoustofluidic microreactor enables a dynamic cell culture to be set up in a miniaturized system while mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…While the increase, in itself, was insufficient to activate the NK cells alone, which is known to occur through calcium signaling, it was shown that the SAW mechanostimulation led to an approximate 1.5-fold enhancement in the expression of lysosomal-associated membrane protein 1 (LAMP-1)—a marker of NK cell degranulation and hence activation—when applied in conjunction with the addition of phorbol 12-myristate 13-acetate (PMA) that is commonly employed to trigger protein kinase C (PKC) signaling for initiating T-cell activation. 327 …”
Section: Applications Of Acoustically Driven Mechanostimulationmentioning
confidence: 99%
“…While the increase, in itself, was insufficient to activate the NK cells alone, which is known to occur through calcium signaling, it was shown that the SAW mechanostimulation led to an approximate 1.5-fold enhancement in the expression of lysosomal-associated membrane protein 1 (LAMP-1)—a marker of NK cell degranulation and hence activation—when applied in conjunction with the addition of phorbol 12-myristate 13-acetate (PMA) that is commonly employed to trigger protein kinase C (PKC) signaling for initiating T-cell activation. 327 …”
Section: Applications Of Acoustically Driven Mechanostimulationmentioning
confidence: 99%
“…It has been shown that ultrasounds, including those of frequency approaching 2 MHz, impacted various mechanosensitive ion channels involved in self‐organization of tissues (Chu et al, 2022; Kim et al, 2022; Wu et al, 2017). In addition to the acoustic effects, cells also respond to various environmental mechanical stimuli, such as compression, substrate stiffness (Biswas, 2020) or shear‐flow (Kim et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The main channel has a round cross section with a diameter of 40 μm. To conserve the flow rate along the direction of the flow, we choose the diameter D 2 of the second-generation downstream channel to follow Murray's law: 37,38 where j is the index for the number of channels in the i + 1-th generation. In our case we only have two channels with equal diameter.…”
Section: Resultsmentioning
confidence: 99%